Relationship Between SES and Academic Achievement of Junior High School Students in China: The Mediating Effect of Self-Concept - Li, Shifeng; Xu, Qiongying; Xia, Ruixue (Frontiers in Psychology, 2020)
Over the past decades, the relationship between family socioeconomic status (SES) and academic achievement in school-age children has been well documented. However, the underlying mechanism of how family SES works on academic achievement remains unclear. In this study, we examine the possible role of self-concept in the relationship between SES and school academic achievement among 345 junior high school students in China. The results showed that both family SES and self-concept were significantly associated with the children’s Chinese and mathematics performance, and family SES was also significantly correlated with self-concept. The mediation analysis showed that self-concept partially mediated the relationship between SES and school academic achievement. These findings suggest that interventions targeting self-concept may be an effective way in which to improve children’s school academic achievement.